2016
DOI: 10.1515/biol-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA-G 14 bp polymorphism and soluble HLA-G level on kidney graft outcome

Abstract: Human leukocyte antigen G (HLA-G) is a non-classical HLA class I protein with various immunosuppressive functions. Besides its profound effect to induce fetal tolerance, HLA-G has been also found to enhance graft acceptance. The aim of the study was to analyse the association between HLA-G 14 bp insertion/deletion polymorphism, soluble HLA-G level and kidney graft outcome in the Slovak population. We investigated 69 kidney transplant recipients aged 27–65 years. Out of this group, 37 recipients developed acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…None of the comorbidities studied were linked to patient survival, whereas TNM staging and 14bp polymorphism revealed a clean association. Disease-specific survival rate (Figures 3 and 4) is significantly diminished, and hazard ratio increased (by up to 14fold) in patients expressing higher levels of HLA-G according to published works (25,26,48,49) (in our case, bearers of the DEL/ DEL genotype). Therefore, tumor cells evade the immune system and proliferate unchecked, leading to disease dissemination and death.…”
Section: Survivalsupporting
confidence: 69%
See 1 more Smart Citation
“…None of the comorbidities studied were linked to patient survival, whereas TNM staging and 14bp polymorphism revealed a clean association. Disease-specific survival rate (Figures 3 and 4) is significantly diminished, and hazard ratio increased (by up to 14fold) in patients expressing higher levels of HLA-G according to published works (25,26,48,49) (in our case, bearers of the DEL/ DEL genotype). Therefore, tumor cells evade the immune system and proliferate unchecked, leading to disease dissemination and death.…”
Section: Survivalsupporting
confidence: 69%
“…Previous published research articles revealed that the DEL allele exerts an effect on the stability and levels of HLA-G mRNA ( 25 , 48 ) and on the levels of soluble HLA-G protein ( 26 , 49 ), and reinforce the notion that the log-additive model is the one that best fits our study, since the high frequency of DEL/DEL patients (50.9%) implies a strong genetic predisposition of this genotype in the development of gastric cancer, tightly related to a high expression of HLA-G: the more DEL is present in the transcript the more the HLA-G mRNA is stabilized and translated.…”
Section: Discussionmentioning
confidence: 99%